Complete genome sequence of a Wenzhou isolate of Tomato Leaf Curl Taiwan virus - LI Fang-fang; XU Fang-cheng; LIU Pei (浙江大学学报. 农业与生命科学版)
The virus isolate wzh was obtained from tomato showing leaf curl symptoms in Wenzhou, Zhejiang Province. The complete nucleotide sequence of a DNA-A-like molecule of wzh was determined. It comprised 2 740 nucleotides and had a typical Begomovirus genome organization, with two ORFs [AV2 and AV1 (CP)] in virion-sense DNA and four ORFs (AC1 to AC4) in complementary-sense DNA, separated by an intergenic region (IR). Sequence similarity searches using the BLAST program showed that wzh had higher sequence similarities with Begomoviruses in Asia than those in other regions of the world. wzh DNA-A shared the highest nucleotide sequence identity (99%) with Tomato leaf curl Taiwan virus (ToLCTWV), and phylogenetic comparisons of wzh DNA-A with 20 other Begomoviruses in Asia also revealed a closer relationship with ToLCTWV. The molecular data above showed that the wzh was an isolate of Tomato leaf curl Taiwan virus.